2016
DOI: 10.3390/s17010054
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Interfacial Platform for Homogeneous Electrochemical Immunoassays Using a Poly(Vinylimidazole)-Modified Electrode

Abstract: In this study, a homogeneous method featuring simple, one-step detection was developed to analyze hippuric acid (HA), a major metabolite of toluene. High sensitivity was achieved with the facile immobilization of poly(vinylimidazole) (PVI) on an indium tin oxide (ITO) electrode. Using a previously developed approach, pentacyanoferrate was coordinated with pyridyl-N ligands, and the redox-active Fe(II/III) centers were bound to Ni(II) ions on the electrode via electrostatic cyanide bridges. The detection was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The use of polymers such as polyaminobenzoic acid endow carboxyl groups on the ITO surfaces and allow surface functionalization with N-hydroxysuccinimide ester, which is highly reactive to the -NH 2 groups of antibody. Choi et al suggested an ITO polymer-modified polyvinylimidazole electrode with Ni (II) ions for the detection of hippuric acid (the toluene metabolite) [126]. Since the Ni (II) ions are highly reactive to the imidazole function, various Ni (II) ions bind to the polymer, thereby facilitating electron transfer to the electrode.…”
Section: Organic Conductive Polymermentioning
confidence: 99%
“…The use of polymers such as polyaminobenzoic acid endow carboxyl groups on the ITO surfaces and allow surface functionalization with N-hydroxysuccinimide ester, which is highly reactive to the -NH 2 groups of antibody. Choi et al suggested an ITO polymer-modified polyvinylimidazole electrode with Ni (II) ions for the detection of hippuric acid (the toluene metabolite) [126]. Since the Ni (II) ions are highly reactive to the imidazole function, various Ni (II) ions bind to the polymer, thereby facilitating electron transfer to the electrode.…”
Section: Organic Conductive Polymermentioning
confidence: 99%
“…Ion attachment is another signal enhancement strategy. Choi et al proposed the polyvinyl-imidazole (PVI) polymer-modified ITO electrode with Ni(II) ions for the homogeneous measurement of hippuric acid known as a toluene metabolite [ 37 ]. Due to the high affinity trait of Ni(II) ions with the imidazole group, numerous Ni(II) ions bind to the polymer, thereby promoting electron transfer to the electrode.…”
Section: Functional Nanomaterials Used As Electrodes and Supportinmentioning
confidence: 99%
“…These devices present several advantages such as high sensitivity, fast response, and low cost of production. Electrochemical glucose biosensors can be fabricated by homogeneous or heterogeneous methods, depending on whether a nanomaterial interferes between the electrode and the enzyme that acts as the signal molecule [ 3 , 4 ]. The development of homogenous biosensors is simple, inexpensive, and exploits the adsorptive capacity and binding ability of the reactants towards the electrode; these biosensors surpass steric hindrance and improve enzymatic efficiency.…”
Section: Introductionmentioning
confidence: 99%